Higher plant vacuolar ionic transport in the cellular context - Pottosin, Igor I.; Muñiz, Jesús (Instituto de Ecología, A.C., 2002)
The vacuole, occupying up to 95% of the volume of a mature higher plant cell, serves as a main store of solutes and as the key element of intracellular Ca2+- and pH-stat. The role of the vacuole in the ionic homeostasis of the cell is also evident under K+-starving conditions and under salt stress. It is involved in the regulation of turgor and cell volume, and in specialized cells, such as stomatal guard cells, a large central vacuole is a principle component of the cell osmotic motor. For more than a decade, the guard cell has gained the status of a higher plant cell model, intensely studied by physiological, cell and molecular biology techniques. Despite tremendous progress in the understanding of signal transduction events taking place at plasma membrane of guard cells, the involvement of vacuolar ion transporters remains a significant challenge. Like in a plasma membrane, the ionic transport across the vacuolar membrane, the tonoplast, is directed and coordinated through a complex set of specific transport proteins, including pumps, transporters, and ionic channels. During recent years, the application of modern electrophysiological techniques (principally, the patch-clamp) has enabled numerous individual ion channels to be functionally characterized, although none of them has been structurally identified. The work of our group is focused on the characterization of so called slow (SV) and fast (FV) vacuolar ion channels, which have a wide, if not ubiquitous, distribution in higher plants, and can be detected in stems, leaves, as well as in root storage tissue. Their ionic selectivity, gating by membrane voltage and by physiologically abundant cations, as well as their possible roles in signal transduction and ionic balance are discussed.